Desain Media Pembelajaran Weblog Kimia Berbasis Sains Teknologi Masyarakat (STM) untuk Mendukung Literasi Sains Siswa - dea zuliana; Fitri refelita (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
ABSTRACT This result aimed at developing a learning media design in the form of Science Technology Society (STS) based Chemistry Weblog learning media in supporting student scientific literacy on Crude Oil lesson. It was Research and Development (R&D) with Borg and Gall model that was limited to the fifth stage. The stages were collecting preliminary data, planning, developing the product, testing the product, and revising. The product of this research was validated by the experts of learning media and material, its practicality was tested Chemistry subject teachers, and student response was also tested at State Senior High School 1 Kampar. STS based Chemistry Weblog learning media in supporting student scientific literacy on Crude Oil lesson was stated proper based on the research findings. It was obtained that the assessment percentages of validation were 92.5% by the experts of material and 93.33% by the experts of media, and the assessment criteria were very valid. The assessment percentage on teacher practicality test was 93.33% with very practical assessment criterion, student response test was 80% and students supposed that the weblog was interesting. It was needed a further research to test the effectiveness of the product.